The Human Will in Judaism The Mishnah's Philosophy of Intention - Eilberg-Schwartz, Howard (Brown Judaic Studies, 2020)
This volume examines the role of intention in the Mishnah. What role does intention play in fulfillment of God's commandments according to the rabbis of Late Antiquity?